MRTX1133 attenuates KRASG12D mutated-colorectal cancer progression through activating ferroptosis activity via METTL14/LINC02159/FOXC2 axis - Junwei Zou; Xiuhua Shi; Zhaoying Wu; Siyuan Zuo; Xiaolei Tang; Hailang Zhou; Yong Huang (Translational Oncology)
Colorectal cancer (CRC) ranks as the third most commonly diagnosed cancer and the second leading cause of cancer-related deaths worldwide. Studies have shown that CRC patients with KRAS mutations, especially KRASG12D, have an increased risk of metastasis. Emerging evidence indicates that long non-coding RNAs (lncRNAs) are crucial in the carcinogenesis and progression of various cancers, regulating multiple biological processes but the link between KRASG12D mutations and lncRNAs in CRC remains unclear. Therefore, this study was designed to identify a novel lncRNA involved in KRASG12D-mutated CRC and to elucidate its molecular mechanisms. The analysis of differentially expressed lncRNAs in the GSE201412 dataset revealed that LINC02159 was significantly upregulated following treatment with the KRASG12D inhibitor MTRX1133 Data from the GTEx database indicated that LINC02159 is highly expressed in CRC tumour tissues and is associated with better patient outcomes. In vitro and in vivo experiments suggest that LINC02159 acts as a tumour suppressor in CRC progression. Specifically, LINC02159 knockdown negated the inhibitory effects of MRTX1133 on tumourigenesis and its promotive effect on ferroptosis in KRASG12D-mutated CRC cells. LINC02159 expression is regulated by METTL14, with METTL14 knockdown decreasing m6A methylation of LINC02159, leading to its increased expression in CRC cells. Additionally, LINC02159 stabilised FOXC2 expression through de-ubiquitination. Rescue experiments further clarified that the METTL14/LINC02159/FOXC2 signalling axis is crucial for the inhibitory effects of MRTX1133 in KRASG12D-mutated CRC. Our study provides novel insights into the therapeutic potential of MRTX1133 in treating KRASG12D-mutated CRC by identifying a METTL14/LINC02159/FOXC2 signalling axis that mediates drug response. Our findings highlight the importance of understanding the molecular mechanisms of lncRNAs in cancer to develop effective targeted therapies.